Identification of In Vivo Metabolites of a Potential Anti-tumor Drug Candidate AMAC, in Rat Plasma, Urine and Feces Samples Using UHPLC/QTOF /MS/MS - Dou, Caixia; Tang, Minghai; Xia, Yuanyuan; Yang, Linyu; Qiu, Xiang; Li, Yong; Ye, Haoyu; Wan, Li (Current Pharmaceutical Analysis, 2021)
Background: Drugs based on natural products targeting the microtubule system remain an important component in cancer therapy. Compound 10, 4-((3-amino-4-methoxyphenyl) amino)-2Hcoumarin, derived from coumarin, showed excellent anti-proliferative activity through directly binding to the colchicine-binding site in β-tubulin, suggesting that it could be a perfect drug candidate for antitumor drug research and development. Identification and structural characterization of metabolites is a critical step of both drug discovery and development research. Objective: Compound 10, 4-((3-amino-4-methoxyphenyl) amino)-2H-coumarin, derived from coumarin. Method: In this study, an efficient and sensitive method using Ultra High-Performance Liquid Chromatography couple with Quadrupole Time of Flight tandem Mass Spectrometry (UHPLC/QTOF/ MS/MS) was successfully established and applied to identify the in vivo metabolites in plasma, urine and feces samples of rats after intravenous administration of Compound 10 with a single dose of 10 mg/kg. Result: A total of eight metabolites (including two phase I and six phase II metabolites) had been detected or tentatively identified in plasma, urine and feces, indicating the prominent metabolic pathways were glucuronidation, demethylation and hydroxylation. In addition, in order to understand the structure of metabolites more accurately, synthesis strategy was used to confirm the metabolite M3. Conclusion: The present study provides important information on the metabolism of Compound 10 in vivo for the first time, which would be helpful for understanding the potential metabolic processes of Compound 10 and paving the way for pharmacology and toxicology research.
Keywords: AMAC